Effect of somatic cell co-culture on cleavage rate and embryo development of in-vitro fertilized goat oocytes - Singh, K P; Saxena, Atul; Kharche, S D; Singh, Praneeta (The Indian Journal of Animal Sciences, 2012)
The present study was undertaken to estimate effect of granulosa cell monolayer and oviductal epithelial cells co- culture on cleavage rate and embryo development of in-vitro matured and fertilized goat oocytes. The oocytes were matured in maturation media (TCM-199). After 27 h, matured oocytes were picked up and denuded and then transferred in fert-TALP medium. The capacitated sperm having concentration of 1×106 live sperm/ml were used for in-vitro fertilization. Oocytes were co-incubated with capacitated spermatozoa for 18 h at 38.5±1°C in an atmosphere of 5% CO2 in humidified air. The fertilized oocytes culture in EDM over their respective cell culture i.e. granulosa cells monolayer and oviductal epithelial cells were obtained for further cleavage rate and embryo development (2, 4, 8, and 8 celled) under steriozoom microscope at every 24 h with 50% replacement of pre-equilibrated EDM media up to 7 days. The cleavage rates with granulosa cells monolayer and oviductal epithelial cells co-culture, 48 h post insemination, were 43.52 and 45.27% respectively for goat oocytes. The present study indicated that both granulosa cell monolayer and oviductal epithelial cells co-culture behaved similarly for cleavage rate of in-vitro matured and fertilized goat oocytes, and oviductal epithelial cells co-culture significantly increased in embryonic development stage from 4 cell to 8 cell stage (4 cell, 8 cell and > 8 cell) as compared to granulosa cell monolayer whereas granulosa cell monolayer co- culture significantly increased the embryonic development of 2 cell stage as compared to oviductal epithelial cells.